2016
DOI: 10.1007/s00262-016-1881-y
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral interferon-gamma increases chemokine production but fails to increase T cell infiltration of human melanoma metastases

Abstract: Introduction Optimal approaches to induce T-cell infiltration of tumors are not known. Chemokines CXCL9, CXCL10, and CXCL11 support effector T-cell recruitment, and may be induced by IFNγ. This study tests the hypothesis that intratumoral administration of IFNγ will induce CXCL9-11, and will induce T-cell recruitment and anti-tumor immune signatures in melanoma metastases. Patients and Methods Nine eligible patients were immunized with a vaccine comprised of 12 class I MHC-restricted melanoma peptides and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 47 publications
2
44
0
1
Order By: Relevance
“…The higher level of FCERG and the MHC class II antigens, HB2B and HB2D, in the F4-T2 tumor suggests a more important immunoreactivity [ 74 ], corroborated by a higher mean Ifng expression and a higher immune cells infiltration in the tumor stroma on histoslides. The higher mean expression level of Cxcl10 relative to that of Ccl2 or Ccl7 in the F4-T2 tumor in comparison with F5-T1 agrees with our analyses of the number of CD8+ versus ED1+ cells infiltrated in the two tumors, and with previous reports that Cxcl10 expression in the TME is associated with a higher level of T-cell infiltration [ 75 ]. Finally, the more substantial increase in Ccl11 expression in F4-T2 than in F5-T1, compared with M5-T1, could also reflect a greater recruitment of leukocytes, in agreement with findings by Wågsäker et al [ 76 ].…”
Section: Discussionsupporting
confidence: 92%
“…The higher level of FCERG and the MHC class II antigens, HB2B and HB2D, in the F4-T2 tumor suggests a more important immunoreactivity [ 74 ], corroborated by a higher mean Ifng expression and a higher immune cells infiltration in the tumor stroma on histoslides. The higher mean expression level of Cxcl10 relative to that of Ccl2 or Ccl7 in the F4-T2 tumor in comparison with F5-T1 agrees with our analyses of the number of CD8+ versus ED1+ cells infiltrated in the two tumors, and with previous reports that Cxcl10 expression in the TME is associated with a higher level of T-cell infiltration [ 75 ]. Finally, the more substantial increase in Ccl11 expression in F4-T2 than in F5-T1, compared with M5-T1, could also reflect a greater recruitment of leukocytes, in agreement with findings by Wågsäker et al [ 76 ].…”
Section: Discussionsupporting
confidence: 92%
“…Melanoma biopsies are segregated into two major subsets such as those infiltrated by T cells and those lacking T cell infiltration-tumors with a T cell-infiltrated phenotype differentially expressed chemokines CCL2, CCL3, CCL4, CCL5, CCL19, CCL21, CXCL9, CXCL10, CXCL11, and CXCL13 whereas all tumors irrespective of the T cell infiltration level expressed detectable levels of CXCL8/IL-8 and CXCL12/SDF-1 [ 11 ]. By screening a panel of MM cell lines in vitro , Harlin and colleagues found that the majority secreted only a restricted set of chemokines in vitro including predominantly CXCL8/IL-8 and CXCL1/Gro-α [ 11 ], which are in line with studies by us and others [ 3 , 11 , 68 , 69 , 70 , 71 ]…”
Section: Chemokines In Cellular Homing and Immune Evasionsupporting
confidence: 63%
“…This differential regulation of receptor subunits is thought to influence the balance between the mitogenic and growth inhibitory effects of IFN-γ [41]. Numerous antitumor effects of IFN-γ have been described, and include the regulation of antigen presentation, promotion of inflammatory and chemotactic signals [42,43], activation and polarization of responding leukocytes, as well as direct antiproliferative [44][45][46] and anti-angiogenic effects [47] (Fig. 1).…”
Section: Ifn-gamma Biologymentioning
confidence: 99%